Evaluation and Effectiveness of Tourism Strategies of Olympics Hosting Cities - Tang, Wenjuan (2009)
The Olympic Games is one of the most important mega-events of the world. On this platform, the human beings do not only peruse “higher, quicker, and stronger”, but also the integration of diverse cultures and the development of the economy. Tourism industry catches people’s attention for its great benefits brought by the Olympic Games. This dissertation focuses on the tourism strategies, the key element to maximize the Olympic tourism profits of the host country. With the main purpose of evaluating different tourism strategies undertaken by previous host cities, this study explores the experience of Sydney, Athens, and Beijing and carefully examines and analyses data collected for 2008 Beijing Olympic Games. Through the research, the effective Olympic tourism strategies are presented in this dissertation, and the recommendation for 2010 London Olympic Games is made as well. This research is expected to perform as reference for further study on the relevant topics.